RECONFIGURING ESG-BASED FINANCIAL SYSTEMS FOR SUSTAINABLE FINANCING MANAGEMENT IN ISLAMIC FINANCIAL INSTITUTIONS: EVIDENCE FROM EMERGING MARKETS - Kursusantyo Dudung Prilaksono; Muhammad Muflih (Accounting Department, Politeknik Negeri Bandung, 2026)
This study examines the urgent need to align financial system architecture with sustainable financing practices in Islamic financial institutions, particularly in emerging markets characterized by structural inefficiencies and fragmentation. The objective of this study is to develop an integrated financial system framework to enhance sustainable financing performance. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines on 40 high-quality peer-reviewed articles, with quality assessment using the Mixed Methods Appraisal Tool (MMAT) and Critical Appraisal Skills Programme (CASP). The findings show that only 12 out of 40 studies integrate more than three system dimensions, and none provides a holistic model. The findings demonstrate a persistent structural fragmentation, where ESG, governance, fintech, and risk dimensions are predominantly examined in isolation rather than as an interconnected system. The results highlight the need for regulatory harmonization among OJK, Bank Indonesia, and DSN-MUI to support ESG and fintech integration in Islamic financial systems. This study introduces a five-dimensional integrated financial system framework that simultaneously links Sharia governance, ESG, fintech, financial system stability, and adaptive risk within a value chain structure.